Analysis of Culture Shock Experienced by The New Students of English Department In Faculty of Letters UMI Makassar - Andi Hudriati; Ratnawati Ratnawati; Riskawati Riskawati (Fakultas Sastra - Universitas Muslim Indonesia, 2017)
This study aimed to know the kinds of culture shock do the new students of English literature find in communication and to find out the kinds of solution to overcome culture shock problems of the new students. The type of this study is qualitative description that is aim to explain about the culture shock experienced by the new students in campus UMI Makassar. Data collected in the form of words in written or oral. The researcher found that there two things in this research. The first are three kinds of culture shock do the new students found in communication, such as, language, culture, and level of context. The second is to find out the kinds of solution to overcome culture shock problems of the new students. Such as, learn the local language, make local friends, be patient, keep an open mind, do things that are familiar to you, and try to accept the condition.